Spirituality relationship to the quality of life of children with cancer in Dr. Sardjito general hospital - Pratiwi, Etik; Mulatsih, Sri; Setiyarini, Sri (International Journal Of Community Medicine And Public Health, 2018)
Background: In Indonesia, the prevalence of cancer up to 1.4 per 1000 population. Acute lymphocyte leukemia is one of type of cancers. Sspirituality is an element that increasing and is recognized by many patients with the disease at an advanced stage. Assessment of spirituality in children acute lymphocyte leukemia had ever done by the researcher before shows that spirituality contributes a positive influence to the coping and the achievement of adaptation. Aim of this research was to know how the relationship between spirituality with quality of life in children with cancer. Methods: This study used a mixed design (mixed method), with sequential explanatory strategy. Quantitative approach to the cross-sectional design and in- depth interviews in qualitative data collection. Research has received permission from the The Medical and Health Research Ethics Committee (MHREC). Results: There is a relationship between spirituality and the quality of life of children with cancer with a total value of p=0.001. Spirituality related to the children quality of life emotional, school, and physical domains with each value of p=0.001, p=0.026, p=0.028. Spirituality is not related to the social domains with p=0.054. Qualitative analysis shows that there are six categories from in-depth interviews, that is namely; prayer as a healing pain, the joy and gratitude; the interaction of the source of happiness; loneliness sadness source; socialitation with the enviroment; seek help in overcoming difficulties. Conclusions: There was correlation between spirituality and quality of life of children with cancer.